Iceland is an episodic source of atmospheric ice-nucleating particles relevant for mixed-phase clouds - Sanchez-Marroquin, A; Arnalds, O; Baustian-Dorsi, KJ; Browse, J; Dagsson-Waldhauserova, P; Harrison, AD; Maters, EC; Pringle, KJ; Vergara-Temprado, J; Burke, IT; McQuaid, JB; Carslaw, KS; et al. (Science Advances, 2020)
This is the final version. Available from the American Association for the Advancement of Science via the DOI in this record. Ice-nucleating particles (INPs) have the potential to remove much of the liquid water in climatically important mid-to high-latitude shallow supercooled clouds, markedly reducing their albedo. The INP sources at these latitudes are very poorly defined, but it is known that there are substantial dust sources across the high latitudes, such as Iceland. Here, we show that Icelandic dust emissions are sporadically an important source of INPs at mid to high latitudes by combining ice-nucleating active site density measurements of aircraft-collected Icelandic dust samples with a global aerosol model. Because Iceland is only one of many high-latitude dust sources, we anticipate that the combined effect of all these sources may strongly contribute to the INP population in the mid- and high-latitude northern hemisphere. This is important because these emissions are directly relevant for the cloud-phase climate feedback and because high-latitude dust emissions are expected to increase in a warmer climate. European Research Council Natural Environment Research Council